Opposing latitudinal patterns of soil carbon fractions in faba bean and mung bean cropping systems - Xiangxiang Wang; Qiong Liu; Liang Wei; Zhenke Zhu; Yakov Kuzyakov; Xuefei Li; Jianping Chen; Tida Ge (Plant and Soil, 2026)

Arachidonic acid matters - Houguo Xu; Xiaoxue Meng; Yuliang Wei; Qiang Ma; Mengqing Liang; Giovanni M. Turchini (Reviews in Aquaculture, 2022)
Throughout the evolution of fish nutrition science, the importance of dietary arachidonic acid (ARA, 20:4n‐6) has been somewhat overlooked, likely due to the polarizing research focus on docosahexaenoic (DHA, 22:6n‐3) and eicosapentaenoic (EPA, 20:5n‐3) acids. Nevertheless, especially during the past two decades, increasing attention has been paid to the requirements and functions of ARA in fish nutrition, and a number of relevant studies have now been conducted on a series of fish species, including both marine and freshwater species. Those studies revealed important and diverse functions of ARA in various physiological processes, such as growth, reproduction, stress resistance, pigmentation, immunity, lipid deposition and bone development. The results of the present review, in addition to providing a state‐of‐the‐art summary of current knowledge, also revealed the complexity of ARA functions in terms of dosages, species, development stage, sex and feeding period, as well as in terms of interaction between ARA and other nutritional or non‐nutritional factors.